Penyuluhan Kesehatan Senam Leher Pada Pengguna Smartphone - Setyaningsih, Rahayu; Nuryanti, Aprilia (Cahaya Pengabdian, 2024)
The process of changing the position of the neck when using a smartphone will position the head down to look at the cellphone screen and maintain that position for a relatively long time. This condition will cause muscle problems and if left untreated, it will become chronic pain. Frequency of smartphone use, purpose of using the smartphone, flexion movements when using the smartphone, and body position are the main factors that can cause neck pain. Some of the problems that arise from using smartphones include the effects of addiction, anti-social behavior, and health problems such as neck pain, muscle fatigue and muscle stiffness. Neck pain is a perception of pain involving the cervical region including spinal structures in the form of invertebral discs, ligaments, muscles, acet joints and the nervous system which is caused by repetitive and accumulative trauma from excessive use of the neck. Global Burden Disease states that neck pain is one of the fourth musculoskeletal problems that causes life suffering due to disability, while neck exercises can overcome one of the complaints caused by smartphone use. The aim is to determine the factors associated with complaints of neck pain when using a cell phone. The method is carried out through face-to-face meetings by the Service team and then discussions are held regarding pain management material. Before being given the counseling material, a pre-test was carried out to determine the initial knowledge of the residents, after that health education was given, then a post-test was carried out to measure the increase in knowledge of Dawis Cempaka residents. The results show that there is an increase in health knowledge regarding neck exercises among smartphone users to reduce pain symptoms. Conclusion The health education activities ran smoothly and the aim of the activity was achieved, namely increasing the knowledge of the Dawis Cempaka community.